Clinical and Radiological Results After Minimally Invasive Transpsoas Lateral Access Surgery for Degenerative Lumbar Stenosis - Coutinho, Thiago Pereira (Global Spine J, 2019)
STUDY DESIGN: Prospective cohort study. OBJECTIVE: The lateral transpsoas access is a retroperitoneal approach for the lumbar spine to perform the lateral lumbar interbody fusion (LLIF), an intersomatic arthrodesis performed with a cage placed on the lateral borders of the epiphyseal ring. The procedure can be used to provide indirect decompression of the nervous structures through the discectomy and restoration of the disc height. The objective of the present study was to evaluate the indirect decompression following LLIF both with radiological and clinical parameters. METHODS: Prospective clinical and radiological study in a single center with 20 patients diagnosed with 1- or 2-level degenerative lumbar stenosis. Radiological analysis on magnetic resonance imaging included foramen height, canal area, canal diameter, and disc height. Clinical outcomes included visual analogue scale (VAS) and Oswestry Disability Index (ODI) collected up to 12 months. Complications and reoperations were recorded. RESULTS: In total, 25 levels were treated. No reoperation was required. Disc height was increased by an average of 25% (P < .001). The canal area increased from 109 to 149 mm(2) (P < .001) and from 9.3 to 12.2 mm (P < .001) in anteroposterior diameter. The foramen area demonstrated the effect of indirect decompression on both sides (P < .001). The height of the foramen showed significant average increase of 2.8 mm (P < .001). The results from VAS and ODI questionnaires confirmed the clinical effect of indirect decompression. CONCLUSION: We observed that indirect decompression by the LLIF method is feasible both radiologically and clinically with a low rate of complications and reoperations.